Online Interprofessional Education (IPE) evaluation for healthcare students as Interprofessional Collaboration (IPC) optimization - Vivi Retno Intening; Yullya Permina; Yusup Erwan Setyanto (Universitas 'Aisyiyah Yogyakarta, 2022)
Interprofessional Education (IPE) is carried out to optimize interprofessional collaboration (IPE) in order to improve the quality of health services. Currently, conventional IPE learning is starting to shift to more flexible online IPE. The aims of this study were to evaluate the implementation of online IPE. This is qualitative research with a phenomenological approach. The study involved 12 facilitators of IPE and four healthcare students. Data collection used focus group discussion (FGD) and semi-structured interviews. Thematic analysis was used in this qualitative study. The results of this study show that online IPE can facilitate interprofessional learning for health students. Technical barriers are the main obstacles to online IPE. Online IPE training for facilitators and an attractive, interactive IPE online curriculum design are needed to ensure IPE online runs optimally.